Peningkatan Kualitas Pembelajaran di Sekolah Dasar melalui Inovasi Media Interaktif: Studi Pengabdian di SDN 2 Ngindeng - Sasongko, Yogi Banar; Nasif, Hifni; Farhah, Farhah; Naufal Dafa, Abdul Karim; Marshandi Abi Nur Y, Achmad Ghovva (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Strengthening the quality of learning at the elementary school level requires adaptive and innovative strategies, especially in the digital era, which demands a more engaging and participatory learning process. This community service activity was carried out at SDN 2 Ngindeng in response to the need to increase teacher capacity in designing and using interactive learning media appropriate to the local context. The main objectives of this activity were: (1) to improve teachers' skills in using interactive media, (2) to increase active student engagement in the learning process, and (3) to foster a culture of simple technology-based learning. The community service methods used included teacher training, mentoring in the implementation of interactive media in the classroom, as well as pre- and post-test-based evaluations of teachers and observations of student engagement. The community service results showed a significant improvement in teacher skills, with an average post-test score of 26 points. Furthermore, student engagement increased from 55% to 82% after the program was implemented. These findings demonstrate that interactive media-based learning innovations can be a strategic solution for improving the quality of elementary education, particularly in areas with limited resources.